ANALISIS PERAWATAN MESIN POMPA SENTRIFUGAL DENGAN METODE RELIABILITY CENTERED MAINTENANCE - Dhimas Antoniohud; Irnanda Pratiwi; Hermanto MZ (Universitas Riau Kepulauan, 2022)
The pump is an energy conversion machine that can move fluid from one place to another through a piping medium by adding energy to the fluid being moved continuously. To find out or minimize the occurrence of pump damage, periodic maintenance is carried out. In the pump type 6P-4021-J which is used in the STG (Steam Turbine Generator) and BB (Coal Boiler) sectors, PT. PUSRI is affected by the dirty condition of the slurry caused by the presence of mud and other so the working efficiency of the pump decreases. Therefore, periodic and routine maintenance or cleaning is required. Maintenance policies that are corrective or reactive, systematic or scheduled, and Condition-Based, all aim to achieve the availability and reliability of equipment and systems by reducing maintenance costs. Reliability Centered Maintenance method is used to analyze the causes of failure with the results of decisions for system maintenance. The critical components of a centrifugal pump include; bearings, seal rings, and impellers. The highest RPN value is the bearing component of 96. The reliability value of the bearing component is 0.468 with an average repair time of 3.32 hours. The recommended maintenance action is to apply lubricant regularly. So that it can reduce wear, prevent corrosion, and control the temperature of the bearing.